In cellulo synthesis of dendrimeric sensors for fluorescence-on imaging of bacterial phagocytosis. Issue 25 (11th November 2021) - Jiang, Feng; Shi, Yilong; Zou, Xiaoxue; Han, Jiahuai; Han, Shoufa
Abstract : Methods for optical tracking of pathogen–host interactions are of biomedical significance. Abstract : Methods for optical tracking of pathogen–host interactions are of biomedical significance. We herein have reported a high molecular weight pH sensor (Den-pH) that is assembled in bacteria and then stably trapped in bacteria irrespective of bacterial membrane potentials. Endowed with acidity-triggered red fluorescence, Den-pH allows signal-on tracking of S. aureus in phagocytosis by macrophages. Intra-bacterial formation of multifunctional optical probes, which offers the advantage of overcoming the liability of conventional potential-sensitive dyes to dissipate from stressed bacteria, offers a new tool to study stressed pathogens.